Outcomes for reverse total shoulder arthroplasty patients at an average of 11.6 Years follow-up: A case series - Christopher A. White; Troy Li; Akshar V. Patel; Bradford O. Parsons; Evan L. Flatow; Paul J. Cagle (Journal of Orthopaedic Reports, 2023)
Background: Reverse total shoulder arthroplasty (rTSA) is a relatively new procedure, only gaining approval in the United States in 2003. For these reasons, we sought to expand upon the breadth of current literature reporting on the long-term outcomes following this increasingly common orthopedic procedure. Case details: An institutional database was utilized to identify patients who underwent rTSA with a minimum postoperative follow-up of ten years. The five patients with the longest follow-up and complete clinical measures were ultimately included. Demographics, patient reported outcomes (Visual Analog Score (VAS), American Shoulder and Elbow Surgeon (ASES), Simple Shoulder Test (SST)), range of motion (Forward Elevation, Internal Rotation, External Rotation), and various radiographic measures were subsequently analyzed. The mean follow-up time was 11.6 ± 1.7 years. Patients saw improvements in VAS (pre-op.: 4.8 vs post-op: 3.2), ASES (pre-op.: 38.0 vs post-op: 58.0), SST (pre-op.: 2.6 vs post-op: 5.4), and Forward Elevation (pre-op.: 124° vs post-op: 142°) scores. However, internal and external rotation decreased by two vertebral levels and 14°, respectively. Only one shoulder failed during this follow-up time requiring revision surgery at 5.8 years. The overall survival was 100.0% and 80.0% at five- and ten-years follow-up, respectively, with a predicted implant survival time of 12.8 ± 1.6 years. Conclusion: Despite its relative novelty, rTSA is proving to be a sustainable procedure for patients with regards to pain, shoulder functionality, and implant survival, however, range of motion may not be completely restored. Overall, rTSA acts as a viable option for patients requiring shoulder replacement.